Strengthening the conservation and digital data management of neglected and underutilized species in Tanzania, Benin, Uganda, and Ghana. - Llanos Herrera, Lizeth; Wahome, Anastasia Mumbi; Githu, Beatrice Wanjiku; Chemutt, Joseph Kipkoech; Mendez, Andres Camilo; Ramirez Villegas, Julian Armando (Bioversity International and International Center for Tropical Agriculture, 2025)
The BOLDER (Building Opportunities for Lesser-known Diversity in Edible Resources) Project under working package 7 implemented a systematic gap analysis of neglected and underutilized species (NUS) across Tanzania, Uganda, Ghana, and Benin to identify underrepresented crop diversity within national gene banks and inform strategic collecting missions. Focusing on the four priority crops selected by each country, the analysis employed a data-driven methodology that combined historical accession records, environmental and socio-economic datasets, and predictive modeling to pinpoint geographic and trait-specific gaps, including accessibility, connectivity, and environmental representativeness. High-confidence gaps were identified as areas where existing collections were sparse, poorly connected, or environmentally unrepresentative, providing clear guidance for targeted field collections to maximize the capture of unique landraces and crop wild relatives. Complementing this analytical work, there were several capacity-building workshops on digital data collection using KoboToolbox, enabling gene bank staff to design, pre-test, and implement fully digitized workflows that capture high-quality passport data, GPS coordinates, and photographic records, thereby improving data accuracy, standardization, and readiness for field missions. The outcomes of these activities include mapped conservation gaps, actionable field collection plans, and enhanced institutional capacity to maintain and utilize digital germplasm data, ensuring that future collecting missions are both evidence-driven and operationally efficient.